A modified fly ash and its preparation method and application

Through the surface modification and compounding technology of fly ash, combined with polystyrene and other materials, efficient modified fly ash is prepared, which solves the problems of high cost and low efficiency of fly ash resource utilization and broadens its application range and improve the flame retardant performance of fireproof boards.

CN118930107BActive Publication Date: 2025-01-10SHAANXI KEYSTONE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411406719.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing fly ash resource utilization technology has the problems of high cost and low utilization efficiency, especially during pickling, alkaline washing or water washing treatment, it requires a large amount of acid liquid, alkaline liquid or industrial water consumption and wastewater is generated.

Method used

By grinding fly ash and performing surface modification treatment, the modified fly ash is prepared by combining the silane coupling agent KH-550 and ammonia alkali white mud, and it is prepared with polystyrene, magnesium aluminum hydrotalcite, etc. Combining materials, fire-retardant boards are prepared to improve their flame retardant properties.

Benefits of technology

It realizes efficient modification of fly ash, broadens its application range, improves the flame retardant performance of fireproof boards, and makes full use of solid waste resources and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a modified fly ash and a preparation method and application thereof, belonging to the technical field of fly ash resource development, first, the preparation method of modified fly ash comprises the following steps: fly ash is ground to obtain fly ash fine powder, and then silane coupling agent KH-550 is used to process fly ash fine powder to obtain amination fly ash, and then ammonia-alkali white mud is stirred and added to amination fly ash, and then after drying, modified fly ash is obtained. The present invention makes full use of the solid waste resources generated in the industrial production process, and then integrates and utilizes to obtain a modified fly ash, and then, based on the above research and discovery, the present invention applies the prepared modified fly ash to the development of a fireproof board, which can be applied to boilers and building outer wall fireproofing and thermal insulation, and the present invention improves the flame retardant properties of the fireproof board finally prepared by improving the modification process of fly ash.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fly ash resource development, and in particular relates to modified fly ash and a preparation method and application thereof. Background Art

[0002] The combustion of coal and biomass in thermal power plants produces a large amount of ash, of which more than 70% of the byproducts are classified as fly ash. In existing power plants, most fly ash is stored in ash ponds or piled on open land as solid waste. Therefore, the resource utilization of fly ash is of great significance for reducing land occupation, alleviating environmental pollution and creating economic benefits.

[0003] In the prior art, fly ash is often acid-washed, alkaline-washed or water-washed for resource utilization. This treatment is actually only to retain and activate the components such as silica and alumina in the fly ash, and then apply it to building materials, soil improvement and water treatment. However, whether it is acid-washing, alkaline or water-washing, a large amount of acid / alkali / industrial water is consumed first, and sewage is inevitably generated. Overall, the utilization of fly ash in the prior art has the problems of high cost (additional sewage treatment is required) and low utilization efficiency. Summary of the invention

[0004] The purpose of the present invention is to provide a modified fly ash for use in fireproof materials and a preparation method thereof, and specifically to develop a fireproof board, which can be used for fireproofing and heat insulation of boilers and building exterior walls. The present invention improves the flame retardant properties of the finally prepared fireproof board by improving the modification process of fly ash, thereby ultimately achieving the purpose of broadening the application scope of fly ash.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing modified fly ash comprises the following steps:

[0007] S1. Grind fly ash through a 200-300 mesh sieve to obtain fly ash fine powder, then stir and add anhydrous ethanol and silane coupling agent KH-550 into pure water, then stir and add 10% by volume acetic acid solution to obtain a treatment liquid, spray the treatment liquid on the surface of the fly ash fine powder, and then stir and dry to obtain amino fly ash;

[0008] S2. After drying, the ammonia-soda mud is ground through a 200-300 mesh sieve to obtain ammonia-soda mud fine powder, and then the ammonia-soda mud fine powder is added to an acetic acid solution with a volume fraction of 10% by stirring, and then amination fly ash is added thereto with stirring, and then the modified fly ash is obtained after drying.

[0009] Furthermore, the fly ash comprises the following components in percentage by mass:

[0010] SiO2 52.82%~57.13%;

[0011] Al2O3 21.30%~23.40%;

[0012] Fe2O3 7.11%~7.53%;

[0013] CaO 4.44%~4.85%;

[0014] K2O 2.09%~2.26%;

[0015] MgO 1.55%~1.80%;

[0016] Na2O 1.12%~1.45%.

[0017] Furthermore, the fly ash comprises the following components in percentage by mass:

[0018] SiO2 55.53%;

[0019] Al2O3 22.64%;

[0020] Fe2O3 7.25%;

[0021] CaO 4.64%;

[0022] K2O 2.22%;

[0023] MgO 1.70%;

[0024] Na2O 1.40%.

[0025] Furthermore, the ammonia-soda white mud comprises the following components in percentage by weight:

[0026] CaCl2 20.15%~23.20%;

[0027] CaCO3 19.32%~21.75%;

[0028] CaSO4 15.50%~18.32%;

[0029] Mg(OH)2 8.23%~9.15%;

[0030] SiO2 7.22%~8.40%;

[0031] Ca(OH)2 6.03%~6.75%;

[0032] Al2O3 1.90%~2.44%.

[0033] Furthermore, the ammonia-soda white mud comprises the following components in percentage by weight:

[0034] CaCl2 22.55%;

[0035] CaCO3 20.52%;

[0036] CaSO4 17.30%;

[0037] Mg(OH)2 8.95%;

[0038] SiO2 8.02%;

[0039] Ca(OH)2 6.58%;

[0040] Al2O3 2.17%.

[0041] Furthermore, the usage ratio of pure water, anhydrous ethanol, silane coupling agent KH-550, 10% acetic acid solution by volume, and fly ash fine powder described in S1 is 1L:100mL:70-80mL:100mL:2-4kg.

[0042] Furthermore, the usage ratio of the acetic acid solution with a volume fraction of 10%, the ammonia-alkali white mud fine powder, and the amination fly ash in S2 is 1L:200-300g:2kg.

[0043] Furthermore, the modified fly ash is prepared by the above preparation method.

[0044] Furthermore, an application of modified fly ash is applied to the field of fireproof boards, and the fireproof boards are prepared by the following steps:

[0045] Add polystyrene, modified fly ash and magnesium aluminum hydrotalcite into pure water and stir, mix and stir for 30 minutes, then add foaming agent and adhesive and stir, mix and stir for 30 minutes to obtain a mixture, inject the mixture into a fireproof board mold, and place it at 35-50°C for foaming and maturation for 7-10 minutes. After foaming and maturation, cool to room temperature to obtain a fireproof board.

[0046] Furthermore, the usage ratio of the pure water, polystyrene, modified fly ash, magnesium aluminum hydrotalcite, foaming agent and adhesive is 20-30 mL: 20-25 g: 85-120 g: 8-15 g: 5-7 g: 12-15 g.

[0047] Furthermore, the foaming agent is n-pentane or isopentane.

[0048] Furthermore, the adhesive is formed by mixing water-based polyurethane and styrene-butadiene rubber in a mass ratio of 1:1.2 to 1.5.

[0049] Beneficial effects of the present invention:

[0050] First, the present invention prepares a modified fly ash. The present invention first uses silane coupling agent KH-550 to perform surface modification on fly ash, improves the dispersibility and compatibility of fly ash, and prepares amination fly ash. Then, ammonia-alkali white mud is added to the amination fly ash as a synergist for compounding. Ammonia-alkali white mud is a waste generated in the production process of soda ash by ammonia-alkali method. The present invention makes full use of solid waste resources generated in the industrial production process and then integrates and utilizes them. Among them, by performing surface amination treatment on fly ash, the coordination effect between amino groups and calcium ions in ammonia-alkali white mud is utilized to improve the dispersibility and interaction of ammonia-alkali white mud in fly ash, and finally obtains modified fly ash. Specifically, the modified fly ash prepared by the present invention contains abundant magnesium hydroxide, calcium carbonate, aluminum oxide and silicon dioxide, among which magnesium hydroxide is an excellent inorganic flame retardant. When heated, magnesium hydroxide decomposes, absorbs heat and releases water vapor, reduces the heat and oxygen supply in the combustion process, and thus achieves a flame retardant effect; calcium carbonate decomposes at high temperature to produce carbon dioxide, which helps to dilute the oxygen concentration in the combustion area; aluminum oxide is a commonly used inorganic flame retardant, and when heated, aluminum oxide can form an insulating aluminum oxide layer, which can block heat and oxygen, and the presence of aluminum oxide improves the flame retardant properties of the modified fly ash; similarly, silicon dioxide can form a stable silicate layer when burned, which can block heat and oxygen, and the presence of silicon dioxide improves the flame retardant properties of the modified fly ash; and the modified fly ash prepared by the present invention contains abundant calcium ions, which can maintain the stability of bound water by exchanging with substances in the environment, and at the same time, the presence of calcium ions helps the surface of the modified fly ash to absorb heat, gasify, and quickly expand, thereby improving the flame retardant properties of the modified fly ash.

[0051] Then, based on the above research and findings, the present invention applies the prepared modified fly ash to develop a fireproof board, which can be used for fireproofing and heat insulation of boilers and building exterior walls. The present invention improves the flame retardant properties of the finally prepared fireproof board by improving the modification process of fly ash.

[0052] Finally, the present invention makes full use of solid waste resources, realizes the coordinated utilization of solid waste resources, broadens the application scope of fly ash, and realizes the resource utilization of ammonia-alkali white mud. DETAILED DESCRIPTION

[0053] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0054] First, the fly ash raw material studied in the present invention is purchased from Guodian Yangzonghai Power Generation Co., Ltd. The manufacturer gives the following percentages of the main components of the fly ash: SiO2 52.82% to 57.13%; Al2O3 21.30% to 23.40%; Fe2O3 7.11% to 7.53%; CaO 4.44% to 4.85%; K2O 2.09% to 2.26%; MgO 1.55% to 1.80%; Na2O 1.12% to 1.45%. The present invention samples and tests the purchased raw materials and uses them as research objects. The research content is specifically shown in the following embodiments. In the sampling results, the main component percentages of the fly ash are as follows: SiO2 55.53%; Al2O3 22.64%; Fe2O3 7.25%; CaO4.64%; K2O 2.22%; MgO 1.70%; Na2O 1.40%.

[0055] Then, the ammonia-soda white mud raw material studied in the present invention was purchased from Yunnan Dawei Ammonia Manufacturing Co., Ltd., and the manufacturer gave the main component percentages of fly ash as follows: CaCl2 20.15%~23.20%; CaCO3 19.32%~21.75%; CaSO4 15.50%~18.32%; Mg(OH)2 8.23%~9.15%; SiO2 7.22%~8.40%; Ca(OH)2 6.03%~6.75%; Al2O3 1.90%~2.44%. The present invention samples and tests the purchased raw materials and takes them as research objects. The research contents are specifically shown in the following embodiments. In the sampling results, the main component percentages of fly ash are as follows: CaCl2 22.55%; CaCO3 20.52%; CaSO4 17.30%; Mg(OH)2 8.95%; SiO2 8.02%; Ca(OH)2 6.58%; Al2O3 2.17%.

[0056] Example 1

[0057] Preparation of modified fly ash:

[0058] S1. Grind the fly ash sampled and studied above through a 200-mesh sieve to obtain fly ash fine powder for standby use. Take 1L of pure water, add 100mL of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 70mL of silane coupling agent KH-550 (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) to the water, stir and mix for 30min, then add 100mL of acetic acid solution with a volume fraction of 10% (prepared by the laboratory), stir and mix for 30min to obtain a treatment liquid, spray the treatment liquid on the surface of 4kg of fly ash fine powder, stir at room temperature for 1h, and then dry at 120°C for 2h after the stirring is completed. After the drying is completed, the amino fly ash is obtained for standby use.

[0059] S2. Dry the ammonia-alkali mud sampled and studied above at 100°C for 24 hours, then grind through a 200-mesh sieve to obtain ammonia-alkali mud fine powder for use, then take 1L of 10% acetic acid solution by volume (prepared in the laboratory), stir 200g of ammonia-alkali mud fine powder therein, stir at room temperature for 1 hour, then stir 2kg of amination fly ash therein, stir at room temperature for 1 hour, after stirring, dry at 50°C for 1 hour, and after drying, obtain modified fly ash.

[0060] Example 2

[0061] Preparation of modified fly ash:

[0062] S1. Grind the fly ash sampled and studied above through a 300-mesh sieve to obtain fly ash fine powder for standby use. Take 1L of pure water, add 100mL of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 80mL of silane coupling agent KH-550 (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) to the water, stir and mix for 60min, then add 100mL of acetic acid solution with a volume fraction of 10% (prepared by the laboratory), stir and mix for 60min to obtain a treatment liquid, spray the treatment liquid on the surface of 2kg of fly ash fine powder, stir at room temperature for 2h, and then dry at 130°C for 3h after the stirring is completed. After the drying is completed, amino fly ash is obtained for standby use.

[0063] S2. The ammonia-alkali mud sampled for study was placed at 120°C for drying for 24 hours, then ground through a 300-mesh sieve to obtain ammonia-alkali mud fine powder for use, and then 1L of 10% acetic acid solution by volume (prepared in the laboratory) was taken, and 300g of ammonia-alkali mud fine powder was added thereto with stirring, and stirred at room temperature for 2 hours, and then 2kg of amination fly ash was added thereto with stirring, and stirred at room temperature for 2 hours. After stirring, it was placed at 60°C for drying for 2 hours. After drying, modified fly ash was obtained.

[0064] Example 3

[0065] Preparation of modified fly ash:

[0066] S1. Grind the fly ash sampled and studied above through a 300-mesh sieve to obtain fly ash fine powder for standby use. Take 1L of pure water, add 100mL of anhydrous ethanol (AR; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 80mL of silane coupling agent KH-550 (98%; purchased from Sinopharm Chemical Reagent Co., Ltd.) to the water, stir and mix for 60min, then add 100mL of acetic acid solution with a volume fraction of 10% (prepared by the laboratory), stir and mix for 60min to obtain a treatment liquid, spray the treatment liquid on the surface of 3kg of fly ash fine powder, stir at room temperature for 2h, and then dry at 130°C for 3h after the stirring is completed. After the drying is completed, amino fly ash is obtained for standby use.

[0067] S2. The ammonia-alkali mud sampled for study was placed at 120°C for drying for 24 hours, then ground through a 300-mesh sieve to obtain ammonia-alkali mud fine powder for use, and then 1L of 10% acetic acid solution by volume (prepared in the laboratory) was taken, and 300g of ammonia-alkali mud fine powder was added thereto with stirring, and stirred at room temperature for 2 hours, and then 2kg of amination fly ash was added thereto with stirring, and stirred at room temperature for 2 hours. After stirring, it was placed at 60°C for drying for 2 hours. After drying, modified fly ash was obtained.

[0068] Comparative Example 1

[0069] Comparative Example 1 is the control group of Example 2, in which the ammonia-soda white mud in Example 2 is removed, and the remaining preparation steps remain the same as those in Example 2, and finally modified fly ash is obtained.

[0070] Example 4

[0071] Preparation of fireproof board:

[0072] 20 g of polystyrene (article number P661727; weight average molecular weight of 150,000; purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), 85 g of modified fly ash prepared in Example 1 and 8 g of magnesium aluminum hydrotalcite (reagent grade; 99%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) were added and stirred into 20 mL of pure water, mixed and stirred for 30 min, and then 5 g of n-pentane and 12 g of adhesive were added and stirred therein, wherein the adhesive was mixed with water-based polyurethane (solid content 40%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) and styrene-butadiene rubber (grade 1502, purchased from Jilin Yunnan Petrochemical Branch of China National Petroleum Corporation) in a mass ratio of 1:1.2. After the addition of n-pentane and the adhesive was completed, mixed and stirred for 30 min to obtain a mixture, which was injected into a fireproof board mold and placed at 35 ° C for foaming and aging for 7 min. After the foaming and aging were completed, it was cooled to room temperature to obtain a fireproof board.

[0073] Example 5

[0074] Preparation of fireproof board:

[0075] 24 g of polystyrene (article number P661727; weight average molecular weight of 150,000; purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), 120 g of modified fly ash prepared in Example 2 and 12 g of magnesium aluminum hydrotalcite (reagent grade; 99%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) were added and stirred into 25 mL of pure water, mixed and stirred for 30 min, and then 7 g of n-pentane and 15 g of adhesive were added and stirred therein, wherein the adhesive was mixed with water-based polyurethane (solid content 40%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) and styrene-butadiene rubber (grade 1502, purchased from Jilin Yunnan Petrochemical Branch of China National Petroleum Corporation) in a mass ratio of 1:1.4. After the addition of n-pentane and the adhesive was completed, mixed and stirred for 30 min to obtain a mixture, which was injected into a fireproof board mold and placed at 50 ° C for foaming and aging for 10 min. After the foaming and aging were completed, it was cooled to room temperature to obtain a fireproof board.

[0076] Example 6

[0077] Preparation of fireproof board:

[0078] 25 g of polystyrene (Article No. P661727; weight average molecular weight 150000; purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), 110 g of modified fly ash prepared in Example 3 and 15 g of magnesium aluminum hydrotalcite (reagent grade; 99%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) were added to 30 mL of pure water with stirring, and the mixture was mixed and stirred for 30 min, and then 7 g of isopentane (99%; purchased from Sinopharm Chemical Reagent Co., Ltd.) and 15 g of adhesive were added with stirring. The adhesive is prepared by mixing waterborne polyurethane (solid content 40%; purchased from Shanghai McLean Biochemical Technology Co., Ltd.) and styrene-butadiene rubber (brand 1502, purchased from Jilin Yunnan Petrochemical Branch of PetroChina Co., Ltd.) in a mass ratio of 1:1.5. After the addition of isopentane and the adhesive, the mixture is stirred for 30 minutes to obtain a mixture, which is then injected into a fireproof board mold and placed at 50°C for foaming and aging for 10 minutes. After the foaming and aging are completed, the mixture is cooled to room temperature to obtain a fireproof board.

[0079] Comparative Example 2

[0080] Comparative Example 2 is the control group of Example 5, in which the modified fly ash prepared by Example 2 in Example 5 is replaced by the modified fly ash prepared by Comparative Example 1, and the remaining preparation steps remain the same as those in Example 5, and finally a fireproof board is obtained.

[0081] Comparative Example 3

[0082] Comparative Example 3 is the control group of Example 5, in which the modified fly ash prepared by the raw material Example 2 in Example 5 is removed, and the remaining preparation steps remain unchanged from Example 5, and finally a fireproof board is obtained.

[0083] Test Case

[0084] The fireproof boards prepared in Examples 4 to 6 and Comparative Examples 2 to 3 were subjected to performance tests. The performance test process is as follows, and the test results are shown in Table 1:

[0085] Combustion performance grade: Refer to 5.1.1 Flat-plate building materials in GB8624-2012 "Combustion performance classification of building materials and products", and conduct testing in accordance with the criteria specified in the combustion performance grade and classification criteria of flat-plate building materials and products in the standard.

[0086] Oxygen index: Test under the specified test conditions in GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test".

[0087] Thermal conductivity: Tested with reference to the hot wire method specified in GB / T10297-2015 "Hot wire method for determination of thermal conductivity of non-metallic solid materials".

[0088] Compressive strength: The test was conducted using an electronic universal testing machine (model INSTRON-5969, produced by Instron Corporation, USA), where the loading speed was set to 0.05 MPa / s.

[0089] Table 1 Test results

[0090] project Example 4 Example 5 Example 6 Comparative Example 2 Comparative Example 3 Combustion performance level A1 A1 A1 A B Oxygen index (%) 28.7 29.2 29.1 27.6 21.8 Thermal conductivity (w / (m·k)) 0.041 0.038 0.039 0.057 0.094 Compressive strength(MPa) 1.07 1.12 1.10 0.84 0.45

[0091] As can be seen from Table 1, the present invention utilizes ammonia-alkali white mud and fly ash to prepare modified fly ash, and then uses the fly ash to develop a fireproof board. After testing, the fireproof board prepared by the present invention has excellent flame retardant properties, thermal conductivity and mechanical properties.

[0092] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing modified fly ash, characterized in that: The following steps are involved: S1. Grind fly ash through a 200-300 mesh sieve to obtain fly ash fine powder, then stir and add anhydrous ethanol and silane coupling agent KH-550 into pure water, then stir and add 10% by volume acetic acid solution to obtain a treatment liquid, spray the treatment liquid on the surface of the fly ash fine powder, and then stir and dry to obtain amino fly ash; S2. After drying, the ammonia-soda mud is ground through a 200-300 mesh sieve to obtain ammonia-soda mud fine powder, and then the ammonia-soda mud fine powder is added to an acetic acid solution with a volume fraction of 10% by stirring, and then amination fly ash is added thereto with stirring, and then the modified fly ash is obtained after drying.

2. The method for preparing modified fly ash according to claim 1, characterized in that: The fly ash comprises the following components in percentage by mass: SiO2 55.53%; Al2O3 22.64%; Fe2O3 7.25%; CaO 4.64%; K2O 2.22%; MgO 1.70%; Na2O 1.40%.

3. The method for preparing modified fly ash according to claim 1, characterized in that: The ammonia-soda white mud comprises the following components in percentage by weight: CaCl2 22.55%; CaCO3 20.52%; CaSO4 17.30%; Mg(OH)2 8.95%; SiO2 8.02%; Ca(OH)2 6.58%; Al2O3 2.17%.

4. The method for preparing modified fly ash according to claim 1, characterized in that: The usage ratio of pure water, anhydrous ethanol, silane coupling agent KH-550, 10% acetic acid solution by volume, and fly ash fine powder described in S1 is 1L:100mL:70-80mL:100mL:2-4kg.

5. The method for preparing modified fly ash according to claim 1, characterized in that: The usage ratio of the acetic acid solution with a volume fraction of 10%, the ammonia-alkali white mud fine powder, and the amination fly ash in S2 is 1L:200-300g:2kg.

6. A modified fly ash, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.

7. An application of modified fly ash, characterized in that: Application of the modified fly ash prepared by the preparation method according to any one of claims 1 to 5 in a fireproof board, wherein the fireproof board is prepared by the following steps: Add polystyrene, modified fly ash and magnesium aluminum hydrotalcite into pure water and stir, mix and stir for 30 minutes, then add foaming agent and adhesive and stir, mix and stir for 30 minutes to obtain a mixture, inject the mixture into a fireproof board mold, and place it at 35-50°C for foaming and maturation for 7-10 minutes. After foaming and maturation, cool to room temperature to obtain a fireproof board.

8. The use of modified fly ash according to claim 7, characterized in that: The usage ratio of the pure water, polystyrene, modified fly ash, magnesium aluminum hydrotalcite, foaming agent and adhesive is 20-30 mL: 20-25 g: 85-120 g: 8-15 g: 5-7 g: 12-15 g.

9. The use of modified fly ash according to claim 7, characterized in that: The foaming agent is n-pentane or isopentane.

10. The use of modified fly ash according to claim 7, characterized in that: The adhesive is prepared by mixing waterborne polyurethane and styrene-butadiene rubber in a mass ratio of 1:1.2 to 1.5.

Citation Information

Patent Citations

  • Composite reinforcement material for solid waste recycling and methods for soil reinforcement using such materials

    BE1031395B1

  • Crosslinked starch modified regenerated EPS particle-portland cement composite foaming insulation plate with water resistance as well as preparation method thereof

    CN106673692A